Maps Berbasis Sensor Lidar untuk Navigasi Tunanetra - Mahdi, Arisul; Marlina, Marlina; Rahmahtrisilvia, Rahmahtrisilvia; Safaruddin, Safaruddin; Purwanto, Wawan (Jurnal Pendidikan Kebutuhan Khusus, 2024)
This article's goal is to describe the evolution of assistive technology, which includes lidar-based maps for mobility blind navigation. This technology serves as a barrier against the difficulties faced by the blind when doing mobility tasks in areas without easily accessible mobility. The ADDIE development method is used in sensor-based mapping projects that cover analysis, design, development, implementation, and evaluation. The development of assistive technology produced a prototype based on lidar sensor technology that was enhanced with a webcam using a Raspberry Phi 4. This map can accurately depict areas and depict nearby obstacles. The device is then outfitted with a webcam camera that uses voice guidance to go to the destination room while reading the QR Code as a direction indicator. The simplified distance units and steps are easily comprehensible for individuals with visual impairments. Based on conducted studies, lidar sensor-based maps have proven to be an excellent tool for blind people requiring interior navigation.